The Mid-Oceanic Ridges Mountains Below Sea Level - Nicolas, Adolphe 1936-2020 (Springer Berlin Heidelberg, 1995)
Over the past 20 years, geologists have come to realize that the real object of their studies is the Earth, and that their favorite subjects, whether basalts, earthquakes, or the Tibetan plateau (for example) are only the means to understanding the Earth itself as a complete entity. Geology has thus acquired aglobai perspective. The study of any particular regional problem is only of general interest in providing good foundations to investigate general phe nomena. But this same particular problem can only be completely understood ifits global context is taken into account. The geology of the Andes is only one of many examples of subcontinental subduc tion and, as such, its study contributes to our understanding of the mechanism of subduction. However, at the same time, understanding the geology of the Andes is today no longer possible without relating it to the geological history of the eastern Pacific, reconstructing the relative movements of the East Pacific Rise and the Nazca Ridge against South America and, in a wider sense, in the context of the his tory of the Pacific Ocean as a whole. Geology today is based on an infinite variety of natural examples which in the general frame of plate tectonics deals with geometrie objects, historie situations, or the various methods employed. The object "Earth" includes not only subjects like seismology, structural geology, and geochemistry, but also studies of the crust, mantle and core, oceans and continents, and mountain ranges and basins